ORGANIZING TEACHING ACCORDING TO THE REQUIREMENTS FOR ELECTRONIC EDUCATIONAL MANUALS (Conference Zone, 2022)
In this article e-learning resource - the essence of the structural elements that determine the structural basis of the systematic e-learning resource for educational disciplines (modules), pedagogical requirements for the creation of e-learning resource, the creation of e-learning resource educational and methodological requirements.